18‐1: Far Field Imaging Through Liquid Crystal Displays for Biometrics. Issue 1 (28th June 2021) - Large, Timothy; Emerton, Neil; Lim, Sehoon; Nuesmeyer, Chris
Abstract : A camera is placed behind a standard liquid crystal display with a backlight that is designed to retain a near‐infra‐red image, while simultaneously delivering diffuse illumination in the visible spectrum. The camera image can be used for system log‐on or continuous authentication, without occupying valuable bezel space.